PERANCANGAN GEDUNG APARTEMEN PALTROW CITY BELLINI TOWER TEMBALANG - Muhammad Irfan; Bastian Triatmojo; Nuroji Nuroji; Hardi Wibowo (Jurnal Karya Teknik Sipil, 2015)
Design structure of high story building by SNI 03-1726-2012 on this final report are designed inseismic zoning area of Semarang city usingthe structure frame system method with configuration structure collapsethe System Bearer Special Moment (SRPMK). This system is planned to use the concept of strong column weak beam, where the vertical elements of the structure (column) should be stronger than the horizontal elements of the structure (beam), to be plastically formed jointsfirst on the beam. The analysis of the structure of high story building by SNI 03-1726-2012 using software help SAP2000 v14 with the results of the analysis are used to determine the fundamental period of the structureand the forces acting on the structure. fundamental structural period must be limited so that the structure is not very flexible.